Increasing doses of a microbial preparation in the health and productive performance of post-weaning pigs - Flores, Luis; Elías, Arabel; Proaño, F.; Granizo, G.; López, Sandra; Caisedo, William (Cuban Journal of Agricultural Science, 2016)
In order to evaluate growing doses of a microbial preparation (milk whey 33 %, molasses 20 %, urea 1 %, mineral salt 1 %, and water 45 %) on the productive performance, and the presence of diarrheas in post-weaning pigs, a completely randomized design was applied, with five treatments and four repetitions: T1 concentrate, T2, T3, T4 (concentrate plus 5 mL kg LW-1, 10 mL kg LW-1, and 15 mL kg LW-1 of the microbial preparation, respectively) and T5 (concentrate plus commercial probiotic). A total of 200 pigs from the crossing of Landrace x Large White with Belgium White x Pietrain were used, with 28 d old and 6.99 kg LW ± 0.18 kg. The highest final weight and the best total and daily weight gain (P < 0.01) were obtained in pigs fed with concentrates, and 15 mL kg LW-1 of the microbial preparation was added. Values of 25.78 kg, 18.78 kg and 447.25 g were obtained, respectively. The most efficient values, according to the conversions of dry matter, protein and energy (P < 0.01), were obtained in the treatment with 15 mL.kg LW-1 of microbial preparation, with 1.68 kg DM.kg-1, 351.16 g.kg LW-1, and 24.54 MJ.kg LW-1, respectively. The lowest presence of diarrheas (P < 0.01) was obtained in animals fed with the concentrate plus 15 mL kg LW-1 of the microbial preparation, and an incidence of 12 diarrheas. The use of the microbial preparation (15 mL kg LW-1) improved the nutritional value of the concentrates, the best parameters were obtained and the appearance of diarrheas was reduced. Key words: probiotic, nutritional quality, pigs, digestibility